Clinical characteristics of patients with autoimmune nodopathy with anti-neurofascin155 antibodies - Zhang, Jiwei; Hou, Xiaotong; Wei, Liting; Liu, Jinshun; Li, Shibo; Guo, Yifan; Liu, Hongbo; Jiang, Yan (Frontiers in Immunology, 2024)
Background: According to the latest guidelines on chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), patients with CIDP with anti-neurofascin 155 (NF155) antibodies are referred to as autoimmune nodopathy (AN), an autoimmune disorder distinct from CIDP. We aimed to compare the clinical data of patients with AN with anti-NF155 antibodies with those of anti-NF155 antibodies-negative patients with CIDP, and to summarize the clinical characteristics of patients with AN with anti-NF155 antibodies. Methods: Nine patients with AN with anti-NF155 antibodies and 28 serologically negative patients with CIDP were included in this study. Diagnosis was made according to the diagnostic criteria in the European Academy of Neurology (EAN)/Peripheral Nerve Society (PNS) guidelines on CIDP published in 2021. Demographics, clinical manifestations, electrophysiological examination, cerebrospinal fluid (CSF) tests, and response to treatment were retrospectively analyzed. Results: Compared with serologically negative patients with CIDP, those patients with AN with anti-NF155 antibodies were younger (p=0.007), had a younger onset age (p=0.009), more frequent ataxia (p=0.019), higher CSF protein levels (p=0.001), and more frequent axon damage in electrophysiology (p=0.025). The main characteristics of patients with AN with anti-NF155 antibodies include younger age and onset age, limb weakness, sensory disturbance, ataxia, multiple motorsensory peripheral neuropathies with demyelination and axonal damage on electrophysiological examination, markedly elevated CSF protein levels, and varying degrees of response to immunotherapy. Conclusions: Patients with AN with anti-NF155 antibodies differed from serologically negative patients with CIDP in terms of clinical characteristics. When AN is suspected, testing for antibodies associated with the nodes of Ranvier is essential for early diagnosis and to guide treatment.